Gaps in terrestrial soundscape research: It's time to focus on tropical wildlife - Scarpelli, Marina D.A.; Ribeiro, Milton Cezar [UNESP]; Teixeira, Fernanda Z.; Young, Robert J.; Teixeira, Camila P. (Elsevier, 2020)
There has been a body of research examining the sounds produced in landscapes. These sounds are commonly defined as soundscapes, however, the term is often used in different contexts. To understand the various meanings attributed to soundscapes, we identified how soundscapes are represented in the scientific literature and identified current knowledge gaps in soundscape research focusing on terrestrial environments. We conducted a quantitative review of published papers with the keyword soundscape available at Web of Science and Scopus databases. A total of 1309 abstracts and a subset of about 5% (N = 68) complete papers and reviews published from 1985 to 2017 were read and analysed, identifying types of sound, types of environment and focal species studied, as well as study regions and climates. By identifying the current focus of research, we also identified gaps and research opportunities. Research was biased towards temperate regions, terrestrial environments, and the impacts on humans in urban areas. Although most of the world's biodiversity is concentrated in tropical wilderness areas, these regions had fewer studies attributed to them. Given the importance of tropical landscapes for biodiversity conservation, we strongly suggest that more research should be undertaken in the tropics, with a particular focus on wildlife in these regions. Furthermore, soundscape research (methods and tools) should increasingly target the anthropogenic impacts on wildlife, including behavioural and physiological changes, alongside the current focus on human-sound interactions and the approach used by bioacoustics methods.
Keywords: Bioacoustics; Gap analysis; Landscape; Noise; Review; Sound